The Contemporary Role for Hip Arthrodesis in Adolescents and Young Adults: Current Concept Review - Dimovski, Radomir; Zaltz, Ira (Journal of the Pediatric Orthopaedic Society of North America, 2021)
There are two modes of surgical treatment for end stage arthritis in the young patient. Hip arthrodesis and arthroplasty are historically proven options. Currently, patient and surgeon related factors influence choice of treatment. Arthrodesis relieves arthritic pain and enables modified function with expected eventual transition to arthroplasty. Advances in arthroplasty implants have increased component survivorship but studies are still needed to determine outcomes using modern implants. Conversion arthroplasty following arthrodesis provides good outcomes with significant functional gain. Primary total hip arthroplasty for young patients is increasingly accepted due to improvements and consistency of implantation and more patient-expected natural levels of function. Data supporting arthrodesis or arthroplasty for young patients with end stage hip arthritis requires further study. This article summarizes the dilemma, provides current data in order to help guide decision-making.